D-entropy: A new approach to the dynamics and evolution of systems - Somsikov, Vyacheslav; Kapytin, Vitaliy; Andreyev, Alexey; Chcherbulova, Ekaterina (International Journal of Innovative Research and Scientific Studies, 2025)
A new concept, D-entropy, is introduced to define the changes in the internal energy of systems moving in non-uniform external force fields. D-entropy is defined solely in terms of the system’s dynamic parameters, specifically as the ratio of the change in internal energy to its total internal energy. It arises from the equation of motion for structured bodies, which accounts for the work done by external forces that not only alter the body’s motion but also modify its internal state. The uniqueness of D-entropy lies in its applicability to both mechanics and thermodynamics, enabling the analysis of evolutionary processes within the framework of physical laws. Kinetic energy and D-entropy are identified as key parameters in the evolution of systems.